The psychological impact of COVID-19 pandemic on healthcare workers - Tong, Fei; Zhang, Lemeng; Huang, Liping; Yang, Hongxia; Wen, Minni; Jiang, Ling; Zou, Ran; Liu, Feng; Peng, Wanglian; Huang, Xufen; Yang, Desong; Yang, Hui; et al. (Frontiers in Public Health, 2022)
Background: As unprecedented and prolonged crisis, healthcare workers (HCWs) are at high risk of developing psychological disorders. We investigated the psychological impact of COVID-19 pandemic on HCWs. Methods: A total of 439 HCWs were enrolled. Anxiety and depression levels were measured using Hospital Anxiety and Depression Scale (HADS). The Post Traumatic Stress Disorder (PTSD) Checklist for DSM-5 (PCL-5) was used to assess the presence and severity of PTSD. Fear was measured by modified scale of SARS. Differences in fear, anxiety, depression and PTSD among HCWs with different clinical characteristics were analyzed. Results: The prevalence of anxiety, depression, and PTSD in HCWs was 15.7%, 9.6%, and 12.8%, respectively. Females and nurses were with higher fear level (P<0.05) and higher PTSD levels (P<0.05). Further analysis of female HCWs revealed that PTSD levels in the 35-59 years-old age group were higher than that in other groups; while married female HCWs were with increased fear than single HCWs. Conclusion: Gender, marital status and age are related to different level of psychological disorders in HCWs. Clinical supportive care should be implemented for specific group of HCWs.